Pengaruh Keterampilan Awak Kapal dalam Penggunaan Peralatan Navigasi terhadap Keselamatan Pelayaran pada PT. Al Jazeera Shipping Co.W.L.L. - Putri Dwi Jayanti; Robertus Noreng (Jurnal Pendidikan Manajemen Transportasi, 2023)
The purpose of this study was to determine how the influence of the skills of the crew in the use of navigation equipment on the safety of the shipping fleet at PT. AL JAZEERA SHIPPING.CO.W.L.L. The population in this study is the crew of a fleet of ships on PT. AL JAZEERA SHIPPING.CO.W.L.L, amounting to 21 people from 7 ships namely Sea Monarch, Sea Thunder, Al Aali 1, Al Faisal 1, Valian Eagle, Sea Dragon, Sea Majestic. The sample used was the entire crew of PT. AL JAZEERA SHIPPING.CO.W.L.L fleet, namely Sea Monarch, Sea Thunder, Al Aali 1, Al Faisal 1, Valian Eagle, Sea Dragon, Sea Majestic, amounting to 21 people with census techniques ". Saturated sampling is done if the population is less than 100 people. Based on the analysis and discussion shows that the skills of the crew in the use of navigation equipment at PT. AL JAZEERA SHIPPING.CO.W.L.L with an average weight of 4.00 so that respondents agreed that the crew was skilled in the use of navigation equipment. Safety of the shipping fleet at PT. AL JAZEERA SHIPPING.CO.W.L.L where the average weight is 4.01 so respondents agree that the safety of the shipping fleet is good. The results of simple linear regression analysis note that the skills of the crew in the use of navigation equipment on the safety of the shipping fleet of PT. AL JAZEERA SHIPPING.CO.W.L.L is very strong and positive, besides that based on the results of the Hypothesis Testing analysis it is found that there is a very strong positive influence on the skills of the crew in the use of navigation equipment on the safety of the shipping fleet at PT. AL JAZEERA SHIPPING.CO.W.L.L.